A Randomized Controlled Trial to Assess the Effectiveness of Muscle Strengthening and Balancing Exercises on Chemotherapy-Induced Peripheral Neuropathic Pain and Quality of Life Among Cancer Patients. Issue 4 (July 2020) - Dhawan, Shelly; Andrews, Rachel; Kumar, Lalit; Wadhwa, Sanjay; Shukla, Garima
Abstract : Background: Chemotherapy-induced peripheral neuropathy (CIPN) is the presence of tingling, burning, itching, and unpleasant sensations in hands and feet due to nerve damage by chemotherapy. Exercise rehabilitation has potential to prevent or alleviate CIPN. Objective: The aim of this study was to assess the effectiveness of muscle strengthening and balancing exercises on CIPN pain and quality of life (QOL) among cancer patients. Methods: The randomized controlled trial included 45 cancer patients from a tertiary care hospital in India receiving chemotherapeutic drugs paclitaxel and carboplatin and found to have CIPN. Subjects were randomly allocated to exercise (n1 = 22) and usual care (n2 = 23) groups. The exercise group received home-based muscle strengthening and balancing exercise for 10 weeks. Data regarding demographic, clinical characteristics, CIPN, neuropathic pain, and QOL were collected by structured questionnaires Chemotherapy-Induced Peripheral Neuropathy Assessment Tool, nerve conduction velocity, Leeds Assessment of Neuropathic Symptoms and Signs pain scale, and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire. Results: The 2 groups were homogenous regarding demographic variables. In clinical characteristics, the exercise group had larger body surface area and received a higher dose of paclitaxel. Significant reduction in neuropathic pain scores ( P < .0001) and improvement in Functional QOL ( P = .0002), Symptom QOL ( P = .0003), Global Health Status QOL ( P = .004) scores were observed after intervention in the exercise group than the usual-care group. Conclusion: Muscle strengthening and balancing exercises are effective in reducing CIPN pain and improving QOL among cancer patients. Implications for Practice: Muscle strengthening and balancing exercises can be used as a complementary therapy for effective management of CIPN. Abstract : Supplemental digital content is available in the text.